PENGARUH AUDIT TENURE, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP AUDIT REPORT LAG - Yunita Kurnia Shanti; Sudarmadi Sudarmadi; Titik Purwanti (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine and obtain empirical evidence regarding the effect of audit tenure, company size and audit quality on audit report lag in property and real estate companies listed on the Indonesia Stock Exchange in the 2018-2022 period. This type of research is quantitative using secondary data. The method of determining the sample used purposive sampling, so that 12 companies were used as research samples for 5 (five) years of observation, with a total sample of 60 samples obtained. Data analysis techniques using eviews version 9. The results obtained show that (1), audit tenure, firm size and audit quality simultaneously have a significant effect on audit report lag, (2) audit tenure have a significant effect on audit report lag,( 3) company size has no effect on audit report lag, and (4) audit quality has a significant effect on audit report lag.